2013
DOI: 10.1371/journal.ppat.1003800
|View full text |Cite
|
Sign up to set email alerts
|

Gene Fitness Landscapes of Vibrio cholerae at Important Stages of Its Life Cycle

Abstract: Vibrio cholerae has evolved to adeptly transition between the human small intestine and aquatic environments, leading to water-borne spread and transmission of the lethal diarrheal disease cholera. Using a host model that mimics the pathology of human cholera, we applied high density transposon mutagenesis combined with massively parallel sequencing (Tn-seq) to determine the fitness contribution of >90% of all non-essential genes of V. cholerae both during host infection and dissemination. Targeted mutagenesis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
175
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 212 publications
(183 citation statements)
references
References 44 publications
8
175
0
Order By: Relevance
“…Deletion of these transporters was found to affect V. cholerae growth under zinc-deficient conditions, including in in vivo adult and infant mouse models, particularly in the presence of the gut microbiota. A recent transposon sequencing screening study indicates that ZnuABC contributes to V. cholerae colonization in the infant rabbit model (25), supporting the notion that zinc transporters are important for the V. cholerae-host interaction. A few bacterial species have been reported to have more than one zinc uptake system (2).…”
Section: Resultsmentioning
confidence: 79%
See 1 more Smart Citation
“…Deletion of these transporters was found to affect V. cholerae growth under zinc-deficient conditions, including in in vivo adult and infant mouse models, particularly in the presence of the gut microbiota. A recent transposon sequencing screening study indicates that ZnuABC contributes to V. cholerae colonization in the infant rabbit model (25), supporting the notion that zinc transporters are important for the V. cholerae-host interaction. A few bacterial species have been reported to have more than one zinc uptake system (2).…”
Section: Resultsmentioning
confidence: 79%
“…V. cholerae El Tor C6706 (25) was used as the wild-type strain in this study. In-frame deletions were constructed by cloning the regions flanking the target genes into suicide vector pWM91 containing a sacB counterselectable marker (26).…”
Section: Methodsmentioning
confidence: 99%
“…Heme is a potential iron source in the intestine and was reported to be present within the cecal fluid of the rabbit intestine (64,65); however, to our knowledge, this has not been assessed in infant mice. Disruption of the three heme receptors in V. cholerae, which prevented heme transport, did not result in a loss of fitness during in vivo competition with the wild type (24).…”
Section: Discussionmentioning
confidence: 93%
“…2), during growth in the host intestine, NlpD's role cannot be filled by EnvC. The increased importance of NlpD for in vivo growth is corroborated by two recent transposon insertion sequencing studies that revealed that nlpD mutants (but not envC mutants) have reduced fitness in the infant rabbit model of cholera (25,37).…”
Section: Bacth Analysis Suggests That Multiple Interactions Occur Amomentioning
confidence: 96%